2015
DOI: 10.1111/1346-8138.13166
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of 234 rosacea patients according to clinical subtype: The significance of central facial erythema in the prognosis of rosacea

Abstract: Rosacea has a wide spectrum of clinical features, which include persistent facial redness, flushing, telangiectasia, inflammatory papules/pustules, hypertrophy and/or ocular features. The prognosis of rosacea according to clinical subtype has not been evaluated. We analyzed the prognosis of rosacea in 234 patients, which included 120 patients with mixed subtype, 75 with the erythematotelangiectatic rosacea subtype and 39 with the papulopustular rosacea (PPR) subtype. The prognosis of rosacea was classified as:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Additional therapeutics include pharmacologically distinct topical and oral agents, administered alone or in combination. A favourable prognosis exists for patients with papulopustular presentation, while patients with underlying persistent erythema or phymata, with or without inflammatory lesions, are much more refractory to treatment . Approved systemic and topical therapies are discussed below; additional experimental therapies are summarized in Table .…”
Section: Targeted Mechanisms Of Current Rosacea Therapeuticsmentioning
confidence: 99%
“…Additional therapeutics include pharmacologically distinct topical and oral agents, administered alone or in combination. A favourable prognosis exists for patients with papulopustular presentation, while patients with underlying persistent erythema or phymata, with or without inflammatory lesions, are much more refractory to treatment . Approved systemic and topical therapies are discussed below; additional experimental therapies are summarized in Table .…”
Section: Targeted Mechanisms Of Current Rosacea Therapeuticsmentioning
confidence: 99%
“…1,7 It is characterized by a chronic course, symptoms exacerbate over time in >50% of patients, and progression from one subtype to another can occur. 1,8 A small percentage of patients (20.9%) experience complete remission (primarily those with the papulopustular subtype) within 6 years of diagnosis. 8 Once considered a disorder limited to the skin, rosacea is now known to be associated with systemic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…1,8 A small percentage of patients (20.9%) experience complete remission (primarily those with the papulopustular subtype) within 6 years of diagnosis. 8 Once considered a disorder limited to the skin, rosacea is now known to be associated with systemic disorders. Rosacea is significantly associated with allergies, respiratory and gastrointestinal tract disorders, metabolic and cardiovascular diseases, major depression, Parkinson's disease, and some cancers.…”
Section: Introductionmentioning
confidence: 99%
“…As a chronic condition with remissions and exacerbations, rosacea requires long‐term treatment: not only to improve signs and symptoms, but also to maintain remission for as long as possible. Besides, little is known about the duration of remission after rosacea treatment …”
mentioning
confidence: 99%
“…Besides, little is known about the duration of remission after rosacea treatment. [22][23][24] Furthermore, patient-reported outcomes, including Patient's Global Assessment (PaGA) (Appendix S1; see Supporting Information) and patient's health-related quality of life (HRQoL) (measured with RosaQoL; Appendix S2; see Supporting Information), are often not assessed in clinical trials. The objective of this study was to compare the efficacy and safety, including investigators' reported outcomes and patientreported outcomes, of doxycycline 40 mg vs. minocycline 100 mg, in papulopustular rosacea over a 16-week treatment period, with 12-week follow-up.…”
mentioning
confidence: 99%